2007
DOI: 10.1016/j.jacc.2007.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Borderzone Contractile Dysfunction Is Transiently Attenuated and Left Ventricular Structural Remodeling Is Markedly Reduced Following Reperfused Myocardial Infarction in Inducible Nitric Oxide Synthase Knockout Mice

Abstract: Expression of iNOS contributes importantly to post-infarction contractile dysfunction and subsequent LV remodeling, suggesting new strategies to combat heart failure resulting from large MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Accordingly, previous reports showed that pharmacological inhibition or genetic inducible NO synthase deficiency in mice leads to infarct size reduction and ameliorated remodeling. [31][32][33][34] NO-dependant cytotoxicity is mediated by NOderived radicals and an inactivation of sulfur/iron-centered enzymes that are crucially involved in metabolic pathways. 35,36 Enlarged infarct size in Foxp3 DTR mice, thus, likely arises partially from a secondary loss of cardiomyocytes.…”
Section: T Reg -Cell Depletion Deteriorates Healing After MImentioning
confidence: 99%
“…Accordingly, previous reports showed that pharmacological inhibition or genetic inducible NO synthase deficiency in mice leads to infarct size reduction and ameliorated remodeling. [31][32][33][34] NO-dependant cytotoxicity is mediated by NOderived radicals and an inactivation of sulfur/iron-centered enzymes that are crucially involved in metabolic pathways. 35,36 Enlarged infarct size in Foxp3 DTR mice, thus, likely arises partially from a secondary loss of cardiomyocytes.…”
Section: T Reg -Cell Depletion Deteriorates Healing After MImentioning
confidence: 99%
“…Thus the expression of both TNF-alpha [48] and iNOS protein [49] have been documented in cardiomyocytes bordering the infarct scar (Fig. 2).…”
Section: The Adjacent Noninfarcted Regionmentioning
confidence: 83%
“…Until such time as these novel therapies achieve a cost/benefit ratio that rivals conventional therapy, it is likely that they will be reserved for patients with larger infarcts who have more to gain from intervention. Immuno of iNOS expression in the adjacent region early and late after MI (from Gilson et al [49] with permission). Panels A&C show low-and high-power (respectively) magnifications of a wild-type (WT) mouse heart on post-myocardial infarction (MI) day 1 doubleimmunostained for myoglobin (brown) and neutrophils (purple).…”
Section: Discussionmentioning
confidence: 99%
“…18 One hundred fifty microliters of gadolinium-diethylenetriamine-pentaacetic acid (Gd-DTPA, 0.1 mg/kg; Magnevist, Bayer Healthcare, Germany) was injected via an indwelling intraperitoneal line, and T 1 -weighted 3-dimensional images were acquired with a flip angle of 50°.…”
Section: Late Gadolinium-enhanced Mrimentioning
confidence: 99%